Chemical Pulps for Kraft Papers from a Mixture of Conifers - Guha, S. R. D.; Singh, Man Mohan (Indian Forester, 1960)
Laboratory experiments on the pulping of a mixture of conifers from the Punjab by the sulphate process for the manufacture of unbleached and bleached kraft papers are described. Encouraging results were obtained.